Bidirectional relations between subjective academic stress, sleep duration, and subjective well‐being among Chinese adolescents: Evidence from a large‐scale longitudinal study - Menghao Ren; Ziyan Zhou; Yueyang Shao; Xiaohang Luo; Xiaomei Yu; Jingran Xu (Applied Psychology: Health and Well-Being, 2026)
Abstract Chinese adolescents are commonly exposed to higher levels of subjective academic stress, which has been shown to be negatively associated with their subjective well‐being (SWB). However, despite preliminary investigations into this association, little is known about the bidirectional relationship between the two, as well as the underlying mechanisms. Using four‐wave longitudinal data collected over 2 years from 10,550 Chinese adolescents aged 12 to 15 years, the present study examined the bidirectional relationship between subjective academic stress and SWB from the perspective of evaluative theories, as well as the mediating role of sleep duration drawing on mind–body unity theory. Random intercept cross‐lagged panel model analyses showed that, at the within‐person level, subjective academic stress and SWB exhibited a significant bidirectional relationship over time, forming a reciprocal cycle. Specifically, increases in subjective academic stress predicted subsequent decreases in SWB, and decreases in SWB predicted subsequent increases in subjective academic stress, with the predictive effects of subjective academic stress on SWB being significantly stronger than the corresponding reverse effects. In addition, sleep duration played a mediating role in the bidirectional relationship between subjective academic stress and SWB, and the mediating effects of sleep duration in the paths from subjective academic stress to SWB were significantly stronger than those in the reverse paths. These findings provide empirical support for evaluative theories and, from a mind–body unity perspective, reveal sleep duration as an important mechanism linking subjective academic stress and adolescents' SWB, offering practical insights for alleviating adolescents' academic stress and promoting their SWB.